YOUTH CENTER DI KOTA PONTIANAK - Nugroho, Faiqah Dhia; Nurhamsyah, Muhammad; Khaliesh, Hamdil (JMARS: Jurnal Mosaik Arsitektur, 2025)
Technological developments in the era of globalization influence the mindset, behavior, and lifestyle of adolescents, including in Pontianak City. The number of adolescents in Pontianak City has the potential for achievement, interests, and talents but also faces challenges such as delinquency, sexual violence, and unemployment. Available facilities are inadequate to support their self-development, creativity, and mental health. This study designs a Youth Center as a place for education, creation, and recreation with a social architecture approach that emphasizes openness and connectivity. The design method refers to the systematic J.C. Jones (1972) through the stages of ideas, information, analysis, synthesis, and evaluation. The design is realized through an open, connected, and interactive architectural design. The building is designed with a clear main mass, an amphitheater as a meeting center for adolescents with various characters in watching performances and green open areas and recreation/sports areas integrated with the site. The application of social architecture principles is reflected in the transparent facade, depicting adolescents and localistic, flexible public spaces, and circulation that connects zones harmoniously, thus forming a spatial identity that supports creativity, collaboration, and adolescent growth